Exploring Classroom Engagement through Learner-Centered Pedagogy at Mabanutan Elementary School - Bareng, Cherry (Azal Arts and Humanities, 2026)
Learner engagement is a critical factor in effective teaching and meaningful learning, particularly at the elementary level where foundational skills and attitudes toward learning are formed. This study explored classroom engagement as shaped by learner-centered pedagogy at Mabanutan Elementary School. Using a qualitative case study design, data were gathered through classroom observations, semi-structured interviews with teachers, and analysis of instructional materials. Findings reveal that learner-centered strategies such as collaborative activities, guided questioning, differentiated tasks, and contextualized instruction enhanced behavioral, emotional, and cognitive engagement among learners. Despite contextual challenges such as limited resources and diverse learner needs, teachers’ adaptive practices and reflective decision-making sustained high levels of participation and interest. The study underscores the importance of learner-centered pedagogy in promoting inclusive and engaging classroom environments and offers implications for instructional practice and school leadership in elementary education. Keywords: learner engagement, learner-centered pedagogy, elementary education, classroom practices, qualitative case study